128 Inspiring the future generation in paediatrics during the pandemic – great ormond street hospital summer school 2020. (16th November 2020) - Liu, Shuang; Smith, Jonathan; Tutt, Abbie; Poisson, Justin; Blackburn, Simon; Costa, Cristine Sortica da
Abstract : Introduction: Great Ormond Street Hospital (GOSH) Summer School aims to inspire medical students and junior doctors to follow a career in Paediatrics, especially given the low competition ratio in Paediatrics training applications in the last three years. This year we had to move the conference to a virtual environment due to the outbreak of COVID-19. Issues: We needed to modify the program to be deliverable as a series of webinars. The Summer School's capacity was increased to 500 participants (Virtually) from 75 (face to face). We explored ways to maintain interactivity, keep engagement, and fulfill our aim to inspire with a much larger group within the virtual environment. Furthermore, we refined our program to reflect the current pandemic. Interventions: To reduce digital fatigue, we changed the length of the conference from 2.5 long days to 4 short days. Each day consisted of 3 or 4 webinars and a career panel session. The career panel sessions focus on sharing the individual journey, which was met with great enthusiasm from the participants. We utilized multiple tools to facilitate the interaction with the participants and speakers: Slido (Q and A, poll and quiz), a conference App, social media, and the 'Raise Hand' tool within Zoom. Measurements: The conference was well attended with zoom data showed 390, 282, 305, and 324 along the four days. Slido showed a high level of engagement with a total of 1005 questions posted and 434 active participants. 344 completed the post-conference survey, 80% voted the conference being excellent, and 100% voted for the continuation of delivering the conference online next year. Lessons Learnt: COVID-19 compelled us to run our conference digitally, however we have gained a great deal of experience in management, leadership, and education. We learned the necessity of making rapid decisions and flexible leadership to enable ourselves to deliver quality education during the pandemic.